Implikasi Manajemen Program Bahasa Arab dalam Mencetak Lulusan Unggul - Abdurrahman Shobirin; Danial Hilmi (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2021)
Good program management refers to each function that has a role in improving the quality and quantity of the program. From some of its functions can have positive implications on the development of students of Arabic in accordance with the vision and mission set by an institution. Madrasah Aliyah Muhammadiyah 1 Plus Malang has several Arabic programs that can support student achievement and the program is packaged in an educational, constructive, and productive management. This study uses a descriptive qualitative approach to look for implications of the functions of Arabic program management consisting of planning, organizing, implementing, controlling, and evaluating. From several implications it was found that the terminology and commitment of Madrasah Aliyah Muhammadiyah 1 Plus Malang to the Arabic language program was able to deliver its graduates to become excellent and competent graduates to compete in the Arabic language field.